An Efficient Privacy Preserving Technique Using Decoy Passwords - Vankamamidi S Naresh, Gannamaneni Siri Venkata Bhanu, (International Journal of Scientific Research and Management (IJSRM), 2017)
As per the rapid growth and essentiality in the field of information security, the data authentication and data access control are the major concerns. Now-a-days many users prefer to share their data through websites are bound to have many security related issues such as leakage of password file. To provide security against cyber threats in the above dimensions We proposed a decoy based passwords system. Honeywords are the Decoy (fake) passwords. If an attacker steals the password file, it will include original password and honeywords and password cracking becomes tougher. Further we improved the flatness of honeyword generation system using masked password generation algorithm based on randomized technique. So, for an adversary it will become harder to distinguish between original password and a honeyword. The administrator gets notification if any illegal login done apart from the genuine user. In this system the main advantage is that sensitive data can’t be viewed by the unauthorized user. For this Identity Based Encryption (IBE) has been implemented. By this, only the user with genuine credentials allowed to view the original data..